2017
DOI: 10.3140/bull.geosci.1668
|View full text |Cite
|
Sign up to set email alerts
|

Fenestrate Bryozoa of the Moniello Formation (Lower-Middle Devonian, NW Spain)

Abstract: Lower-Middle Devonian non-fenestellid fenestrate bryozoans of NW Spain are reported, from two coastal sections of the upper Emsian-lower Eifelian Moniello Formation, the type locality at Moniello Inlet and at Arnao. Eighteen species of non-Fenestellidae fenestrates belonging to thirteen genera and six families have been identified; nine species are new: Bashkirella arnaoense, Utropora parva, Bigeyina cantabrica, B. spinosa, Fenestrapora elegans, Paraseptopora geometrica, P. irregularis, Kalvariella antiqua and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Unlike the bryozoans described by Suárez Andrés and Wyse Jackson (2017), the upper Emsian crinoid faunas are dominantly endemic to Spain. Only 27% (3 of 11) of the crinoid species from the Moniello Formation co-occur in Germany (e.g., Amblacrinus rosaceus [Roemer, 1844], Gasterocoma antiqua Goldfuss, 1839, and Halocrinus nodosus [Sandberger and Sandberger, 1856]).…”
Section: Devonian Spanish Crinoids In Time and Spacementioning
confidence: 71%
See 1 more Smart Citation
“…Unlike the bryozoans described by Suárez Andrés and Wyse Jackson (2017), the upper Emsian crinoid faunas are dominantly endemic to Spain. Only 27% (3 of 11) of the crinoid species from the Moniello Formation co-occur in Germany (e.g., Amblacrinus rosaceus [Roemer, 1844], Gasterocoma antiqua Goldfuss, 1839, and Halocrinus nodosus [Sandberger and Sandberger, 1856]).…”
Section: Devonian Spanish Crinoids In Time and Spacementioning
confidence: 71%
“…Only 27% (3 of 11) of the crinoid species from the Moniello Formation co-occur in Germany (e.g., Amblacrinus rosaceus [Roemer, 1844], Gasterocoma antiqua Goldfuss, 1839, and Halocrinus nodosus [Sandberger and Sandberger, 1856]). None occurs beyond the Rhenish-Bohemian Province of the Old World Realm (see Boucot et al, 1967, 1969; Suárez Andrés and Wyse Jackson, 2017). Similarly, only 7% (2 of 27) of species in the Santa Lucia Formation occur outside Spain (three from Germany and one from Laurentia).…”
Section: Devonian Spanish Crinoids In Time and Spacementioning
confidence: 99%
“…Rodríguez et al (2010) described the reefal processes shown in the Guadámez-2 section. In contrast to the bryozoan faunas of SW Spain, those from the Lower-Middle Devonian of NW Spain were more intensively studied in a series of publications in more than two last decades (Suárez Andrés, 1998, 1999a, 1999b, 1999c, 2014Suárez Andrés & González Álvarez, 2000;Suárez Andrés & McKinney, 2010;Ernst, 2010Ernst, , 2011Ernst, , 2012Ernst et al, 2011Ernst & Buttler, 2012;Suárez Andrés & Ernst, 2015;, 2021, 2017, 2018Sendino et al, 2019). These studies show the high diversity and richness of bryozoans in the Lower to Middle Devonian sediments of Spain.…”
Section: Introductionmentioning
confidence: 99%